(untitled) (Revista Logos Ciencia & Tecnología, 2018)
This paper proposes a model for the evaluation of maturity in project management for SMEs in the graphic arts sector. The results obtained, through the analysis of main components and the analysis of conglomerates, account for the possibility, and necessity, of creating models of maturity that help the business growth of small organizations. The model evaluates 40 indicators that are grouped into 17 factors that, in turn, are grouped into 5 categories.